Geometric data access for scientific and engineering databases - Sourina, Olga. (2009)
This dissertation studies how to enrich the existing database technology by introducing geometry at the conceptual level of data queries, proposes a geometrie model for accessing and manipulating multidimensional data in scientifie and engineering databases, implements the proposed model in a geometrie query system prototype, and applies this system for solving the problem of materials selection in product design.